2006
DOI: 10.1016/j.jmb.2006.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Halothiobacillus neapolitanus Carboxysomes by Cryo-electron Tomography

Abstract: Carboxysomes are polyhedral bodies consisting of a proteinaceous shell filled with ribulose 1,5-bisphosphate carboxylase/oxygenase (RuBisCO). They are found in the cytoplasm of all cyanobacteria and some chemoautotrophic bacteria. Previous studies of Halothiobacillus neapolitanus and Nitrobacter agilis carboxysomes suggest that the structures are either icosahedral or dodecahedral. To determine the protein shell structure more definitively, purified H. neapolitanus carboxysomes were re-examined by cryo-electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 35 publications
12
144
1
Order By: Relevance
“…32 How the interior of the carboxysome is organized relative to the shell is understood only in rough terms. 23,24 Two recent studies have highlighted the role of the CcmM protein in the b-type carboxysome in binding several other carboxysome proteins, 28,29 including the CcmK shell proteins. 29 The structural details of these interactions have not been illuminated yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 How the interior of the carboxysome is organized relative to the shell is understood only in rough terms. 23,24 Two recent studies have highlighted the role of the CcmM protein in the b-type carboxysome in binding several other carboxysome proteins, 28,29 including the CcmK shell proteins. 29 The structural details of these interactions have not been illuminated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cryo-electron tomography studies provided important insights into the architecture of carboxysomes by showing that this bacterial microcompartment has a nearly icosahedral shape. 23,24 In complementary work, X-ray crystallographic studies have revealed the atomic structures of homologous BMC-type shell proteins from both types of carboxysome, including CcmK2 and CcmK4 from the b-carboxysome 6,7 and CsoS1A from the a-carboxysome. 7 The various carboxysome shell BMC proteins all form hexamers having a narrow central pore bearing a positive electrostatic potential.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the poliovirus-receptor-liposome complexes, it made no difference which standard was used because these complexes happen to adopt a very uniform distribution of orientations (data not shown). For other biological samples, it might have made a difference if, for example, the particles adopt a preferred orientation, as has been observed in many single particle studies and in other tomographic studies (Cardone et al, 2007;Schmid et al, 2006).…”
Section: Classificationmentioning
confidence: 90%
“…Alignment of volumes affected by the missing wedge to an external reference that has no missing information (i.e., it is not altered by the presence of a missing wedge) is addressed in Frangakis et al (2002) by constraining the calculation of the crosscorrelation score to regions of reciprocal space where measurements are available. The more general problem of aligning two volumes affected by the missing wedge was considered in Schmid et al (2006) where the cross-correlation score was scaled with the reciprocal of the number of non-zero terms in the complex multiplication, i.e., the size of the region in Fourier space where information from both volumes is available. More recently, Förster et al (2008) have also studied this case but only in the context of classification (not for alignment), extending the constrained cross-correlation initially proposed in Frangakis et al (2002) to account for the missing wedge of both volumes.…”
Section: Sub-volume Alignment In Tomographymentioning
confidence: 99%
“…More recently, Förster et al (2008) have also studied this case but only in the context of classification (not for alignment), extending the constrained cross-correlation initially proposed in Frangakis et al (2002) to account for the missing wedge of both volumes. The approaches taken in Frangakis et al (2002), Förster et al (2005), Schmid et al (2006) and Förster et al (2008), all rely almost exclusively on exhaustive search of the rotational space to determine the best matching orientation between the two volumes, precluding the analysis of very large data sets. Although in some cases the search may be restricted by exploiting the geometry of the problem, e.g., by only searching for in-plane rotations (Winkler and Taylor, 1999;Förster et al, 2005), this is still a very computationally demanding procedure.…”
Section: Sub-volume Alignment In Tomographymentioning
confidence: 99%